Case Report: Managing Dengue Fever at Home - Fitriadi, Yogi (Faculty of Medicine, Public Health, and Nursing, 2021)
The patient is 6 years old male child, the patient went to the clinic with his parents, complaints of fever since three days ago. The fever goes up and down, reduce with administration of fever medication. The patient complained of nose bleeds 2 times, accompanied by headache. headache feels throbbing, felt constantly, and decreases with rest. The Complaints are not accompanied by coughs, sneeze, dyspnea, epigastric pain, nausea, vomiting, black stool and bloody urine. Patients still want to eat and drink. The patient has no history of traveling out of town in the past 2 weeks.The patient's mother has no history of high blood pressure and diabetes during pregnancy. The patient was born via vaginal delivery, the patient's body weight was 3250 grams. The patient was born in a healthy condition, received Hb0 immunization and vitamin K injection. The patient was treated with his mother after birth. Complete immunization history of patients according to age. Patients attend basic and mandatory immunization programs from the government.The patient is the only child of the marriage of the father and mother. The patient's father and mother are still alive, with a complete history of immunizations, now living together with his parents and grandparents. The patient's home is 8x15 meters, with tiled floors, walls made of walls, water sources are obtained from water drink company. Ventilation and home lighting is quite good. The house looks neat and not dirty. There was no visible tub of open water. The bathroom uses a shower.